CHILD DISCIPLINE EDUCATION CONCEPT IN THE PERSPECTIVE OF BUKHARI HADEETHS (International Conference on Social and Islamic Studies, 2021)
Self-discipline is one of the fundamental characters in education. The elementary school age is a critical age in child education. This research aims to extract the educational concept within Bukhari’s hadeeths. This research employs a qualitative method through quasi experiment. The result shows the concept of child discipline education in Bukhari’s hadeeths pervades educator elements, material aspects, methods and character indicators. In details, educators are parents, teachers and community; material aspects are moral/religion, environment and hidden curriculum; methods are reward and sanction, habituation, discussion and role model; character indicators are obedience, responsibility, absence from bullying and good manner and attitude.